2021
DOI: 10.46827/ejes.v8i12.4007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Use of Geogebra on Student’s Mathematical Representation Skills and Attitude

Abstract: <p>Mathematics is important and applies to science, technology, society or the natural sciences. It is applied directly or indirectly. Most students find this to be a very stimulating, complex, and well-understood subject. Maths in high school is extremely important. The study was designed to investigate the impact of students' mathematical representation skills and their attitudes towards GeoGebra. This study was quasi-experimental and carried out on high school students. We have two groups belonging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Previous research found that GeoGebra offers a dynamic and engaging learning environment [30] [31], with a positive impact on students' attitudes, interest in and learning motivation, and it assists students in visualizing abstract geometry concepts [32]. Zulnaidi [33] reported an increase in interest and learning outcomes of spatial geometry using GeoGebra.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research found that GeoGebra offers a dynamic and engaging learning environment [30] [31], with a positive impact on students' attitudes, interest in and learning motivation, and it assists students in visualizing abstract geometry concepts [32]. Zulnaidi [33] reported an increase in interest and learning outcomes of spatial geometry using GeoGebra.…”
Section: Literature Reviewmentioning
confidence: 99%